The syndemic of HIV, HIV-related risk and multiple co-morbidities among women who use drugs in Malaysia: Important targets for intervention. - Loeliger, Kelsey B; Marcus, Ruthanne; Wickersham, Jeffrey A; Pillai, Veena; Kamarulzaman, Adeeba; Altice, Frederick L (Addictive behaviors, 2015)
Substance use and HIV are syndemic public health problems in Malaysia. Harm reduction efforts to reduce HIV transmission have primarily focused on men with substance use disorders.